Principle for Possible Memory Structures with Extra High Density by Using the Electron Sharing Mechanisms of Atoms in an Inflective Orbit - Sengor, T. (SPIE-INT SOC OPTICAL ENGINEERING, 2014)
Both of the qualitative and quantitative knowledge of electromagnetic fields in the inter-atomic scale bring useful applications. From this point of view, bringing some possible new sights and solutions to atom-electron-photon-atom and/or molecule interactions is aimed in the near-field at inter atomic scale and their potential applications. The electron sharing processes between neighbor atoms are considered as an inflective surface system and an inflective guiding processes. The critical pass and transition structures are derived. The structures involving trigging that transition mechanisms may be suitable to design extra high density and fast data storage processes. The electron sharing processes between two near atomic system are modelled with gate mechanisms involving two distinct passages: continuous pass and discontinuous pass. Even if the stochastic processes are applicable at these cases theoretical approach putting an influence like inner and external dipole mechanisms fits best to the situation and provides almost deterministic scheme, which has potential to estimate some processes being able to design new electronics structures and devices. We call orbitron all of such structures and/or devices. The boundary value problem of atomic system sharing an electron in the way of electron passage model is formulated in inflective spherical coordinate system. The wave phenomenon is studied near spherically inflection points. The analytical essentials are derived for the solution of Helmholtz's equation when inflective boundaries are included. The evaluation is obtained by the extracted separation method. The results are given by using the spherically inflective wave series. The method is reshaped for the solution of Schrodinger equation.
Keywords: quantum electrodynamics; atomic interactions; Casimir-Polder potential; nanoscience; extra high density data storage processes; fast data storage processes; electron transitions; nanoelectromagnetic; POINTS; Optics; Imaging Science & Photographic Technology